Resolusi Manajemen Konflik (Kajian Manajemen Konflik di Lembaga Pendidikan Islam) - Bashori, Bashori; Muhammad Anggung Manumanoso Prasetyo (Penerbit STKIP PGRI Bangkalan, 2020)
In the dynamics of Islamic education institutions, there must be turmoil or conflict, both individual conflicts and group conflicts. Admittedly or not, Islamic education institutions, especially Islamic boarding schools and madrasah, have a high probability of conflict compared to other educational institutions. From this assumption, this paper aims to analyze the role of conflict management in resolving conflicts that occur within the scope of Islamic education institutions. Based on the study of theory, it can be concluded that conflict management is very central in developing conflicts in Islamic boarding schools and madrasah educational institutions as a way to develop Islamic education institutions for the better. Based on that statement, the main concern in reaching conflict is that conflict cannot be avoided. Therefore, controlling conflict becomes a necessity in order to achieve goals in Islamic education institutions.